х=5
Объяснение:
lg5-lg10=lg(x-3)-lg(3x+1)^1/2
lg5/10=lg(x-3)/(3x+1)^1/2
5/10=(x-3)/(3x+1)^1/2
5(3x+1)^1/2=10(x-3)
5√3x+1=10(x-3) |:5
√3x+1=2(x-3)
√3x+1=2x-6 ↑²
3x+1=(2x-6)²
3x+1=4x²-24x+36
4x²-27x+35=0
D=729-560=169
x1=(27+13)/8=5
x2=(27-13)/8=1,75
ОДЗ:
1)х-3>0
х>3;
2)3х+1>0
3х>-1
х>-1/3
Відповідь: х=5
х=5
Объяснение:
lg5-lg10=lg(x-3)-lg(3x+1)^1/2
lg5/10=lg(x-3)/(3x+1)^1/2
5/10=(x-3)/(3x+1)^1/2
5(3x+1)^1/2=10(x-3)
5√3x+1=10(x-3) |:5
√3x+1=2(x-3)
√3x+1=2x-6 ↑²
3x+1=(2x-6)²
3x+1=4x²-24x+36
4x²-27x+35=0
D=729-560=169
x1=(27+13)/8=5
x2=(27-13)/8=1,75
ОДЗ:
1)х-3>0
х>3;
2)3х+1>0
3х>-1
х>-1/3
Відповідь: х=5